Real-world evidence to assess the effectiveness of platelet-rich plasma in the treatment of knee degenerative pathology: a prospective observational study. (June 2022) - Sánchez, Mikel; Jorquera, Cristina; de Dicastillo, Leonor López; Fiz, Nicolás; Knörr, Jorge; Beitia, Maider; Aizpurua, Beatriz; Azofra, Juan; Delgado, Diego
Objective: The present work aims to analyse the effectiveness of platelet-rich plasma (PRP) in degenerative knee pathology based on real-world data and to evaluate possible factors influencing the response to treatment. Methods: In total, 531 cases were analysed collecting data on gender, age, body mass index, pathology location, severity, number of cycles and route of administration. Clinical outcome was evaluated at 6 and 15 months after treatment, using the Knee injury and Osteoarthritis Outcome Score (KOOS) and obtaining percentages of Minimal Clinically Important Improvement (MCII). Blood and PRP samples were randomly tested as a quality control measure to ensure the correct properties. Comparative statistical tests and multivariate regression were performed for the analysis of the variables. Results: The PRP applied had a platelet concentration factor of 1.67, with no leukocytes or erythrocytes. The percentage of patients with MCII at 6 and 15 months after PRP application was 59.32% and 70.62%, respectively. Patients with MCII were younger ( p  = 0.0246) and with lower body mass index ( p  = 0.0450). The treatment had a better response in mild/moderate cases than in severe cases ( p  = 0.0002). Intraosseous PRP application in severe cases improved the effect of intraarticular PRP ( p  = 0.0358). The application of a second cycle of PRP only improved the response in patients without MCII at 6 months ( p  = 0.0029), especially in mild/moderate cases ( p  = 0.0357). Conclusion: The applications of PRP in degenerative knee pathologies is an effective treatment, but this effectiveness nonetheless depends on several variables. Real-world data can complement that from clinical trials to provide valuable information.